2015
DOI: 10.1016/j.bbr.2015.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous testosterone levels are associated with neural activity in men with schizophrenia during facial emotion processing

Abstract: Growing evidence suggests that testosterone may play a role in the pathophysiology of schizophrenia given that testosterone has been linked to cognition and negative symptoms in schizophrenia. Here, we determine the extent to which serum testosterone levels are related to neural activity in affective processing circuitry in men with schizophrenia. Functional magnetic resonance imaging was used to measure blood-oxygen-level-dependent signal changes as 32 healthy controls and 26 people with schizophrenia perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Specifically, the left IFG and right hippocampus showed increased activation upon viewing angry faces in the raloxifene group . This is particularly informative given that we have previously reported hypoactivation of the left IFG in people with schizophrenia relative to healthy controls during angry face processing, and abnormal activity in the cortex (including the IFG) is associated with cognitive processing deficits in schizophrenia . The activating effects of raloxifene in the hippocampus are congruent with its well‐established role in emotion processing and hippocampal hypoactivity found during emotion‐recognition tasks in people with schizophrenia .…”
Section: Evidence That Sex Steroid Manipulations Can Be Useful Adjuncsupporting
confidence: 70%
See 1 more Smart Citation
“…Specifically, the left IFG and right hippocampus showed increased activation upon viewing angry faces in the raloxifene group . This is particularly informative given that we have previously reported hypoactivation of the left IFG in people with schizophrenia relative to healthy controls during angry face processing, and abnormal activity in the cortex (including the IFG) is associated with cognitive processing deficits in schizophrenia . The activating effects of raloxifene in the hippocampus are congruent with its well‐established role in emotion processing and hippocampal hypoactivity found during emotion‐recognition tasks in people with schizophrenia .…”
Section: Evidence That Sex Steroid Manipulations Can Be Useful Adjuncsupporting
confidence: 70%
“…Impaired social functioning in patients with schizophrenia may be related to brain hypoactivation in response to facial emotion processing in frontal and limbic systems . We reported that inferior frontal gyrus (IFG) activity was positively correlated to peripheral testosterone levels in men with schizophrenia during a facial emotion identification task . Conversely, we also reported that circulating testosterone levels were inversely related to brain activation in the middle frontal gyrus and left insula during an emotional response inhibition task in men with schizophrenia .…”
Section: Effects Of Sex Steroid Hormones On Adolescent Brain Developmmentioning
confidence: 81%
“…From the data presented, it turns that a combination of strength and endurance exercises results in both the increase in circulating somatotropic and plasma testosterone concentrations with positive effects on depression, schizophrenia, anxiety, bipolar affective disorder, improvement of the psychosocial state of well-being. If for testosterone the mechanism of action appears to be improving activity in the lower left front gyrus [16] about the somatotrope it is known that growth hormone deficiency in the childhood is manifested by abnormalities of the white matter in the tough body and the corticospinal tract, low volume thalamus and basal nuclei, which is associated with a deficiency of cognitive functions and motor performance [17]. Probably, therefore, the somatotrope exerts a morpho-functional stimulation effect on some subcortical areas, while testosterone exerts the same effect on some cortical areas, and the synergistic effect is not excluded.…”
Section: Discussionmentioning
confidence: 99%
“…In men with schizophrenia, circulating testosterone causes improvement in social functionality, improving activity in the lower left anterior gyrus [8].…”
Section: Corresponding Authormentioning
confidence: 99%
“…Studies investigating the relationship between testosterone levels and schizophrenia symptom severity suggest that testosterone can mediate clinical aspects of the disorder. Low testosterone levels are associated with greater negative symptoms [3, 6, 10, 11], worse cognition [8], and impaired emotion processing [12, 13] in males with schizophrenia. A single clinical trial found that testosterone augmentation ameliorated negative symptoms in men with schizophrenia [14].…”
Section: Introductionmentioning
confidence: 99%